Teachers’ Strategies In Managing Learning For Early Childhood Students From Diverse Religious Backgrounds At Tk Kalibening 2 Wonosobo - Khusnul Musyarofah; Bambang Sugiyanto; Robingun Suyud El Syam (FKIP UNSULTRA, 2026)
This study was motivated by the religious diversity among students at TK Kalibening 2 Wonosobo, which requires teachers to implement inclusive learning practices and foster tolerance from an early age. The study aimed to analyze teachers’ strategies in managing learning activities involving children from different religious backgrounds. This research employed a qualitative approach with a descriptive design. The research subjects consisted of the principal, teachers, and parents. Data were collected through observation, interviews, and documentation. Data validity was ensured through source and technique triangulation, while data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that teachers implemented habituation, role modeling, collaborative play, storytelling, singing, and question-and-answer activities to promote tolerance among children. Learning activities were planned through inclusive and general approaches that accommodated students from different religious backgrounds. During Islamic religious activities, non-Muslim students were provided with alternative activities under teacher supervision. The main challenges included teachers’ limited knowledge of non-Muslim religions, the lack of diversity-based learning training, and young children’s limited understanding of religious differences. These challenges were addressed through communication with parents, teacher supervision, and simple explanations regarding religious diversity. The study found that tolerance can be effectively developed through daily interactions, habituation, and inclusive learning experiences. The novelty of this research lies in its focus on teachers’ strategies for managing learning in an early childhood classroom with students from different religious backgrounds. The findings contribute to the development of multicultural and inclusive education practices in early childhood education.